Prospects of skill development in livestock and allied sector in India for retaining youth in agriculture - Tiwari, Rupasi; Roy, Rakesh; Dutt, Triveni (Indian Farming, 2018)
At present, 263 million people (54.6%) are engaged in the agriculture sector and over half of them are now agriculture labourers (Census, 2011). The total agricultural workers are expected to decline to 190 million by 2022 (expected decline 33%). In agriculture sector, about 18.5% of the workers were skilled in 2009-2010 of which less than 0.5% have formal technical education. These facts reveal an urgent need to educate the Indian population of the importance of skill development and formal technical education in various areas of agriculture and the employability of the sector especially the animal husbandry subsector. This will not only attract back the farmers towards agriculture but also the next generation youth.